(untitled) (Research, Society and Development, 2023)
Thyroid cancer is the most common type affecting the head and neck, predominantly impacting women three times more than men. This pathology arises with the growth of nodules (tumors) in the thyroid. Although its primary cause remains unknown, individuals with certain risk factors may be more vulnerable to developing this disease than others. Risk factors include a family history of cancer, age between 30 and 50, female gender, childhood exposure to radiation, and a diet deficient in iodine. Early detection is crucial for a favorable prognosis, with diagnosis primarily conducted through thyroid gland ultrasound, serum calcitonin level assessment, and fine-needle aspiration biopsy (FNAB). Clinical symptoms such as slow-evolving neck nodules, pain in the anterior neck region, hoarseness or changes in vocal tone, dysphagia, dyspnea, and cough should also be evaluated. Treatment depends on the type and classification of the cancer but may involve surgery (partial or complete thyroidectomy), radioactive iodine therapy, external radiation, and chemotherapy. In search of understanding the incidence of this cancer in Brazilian women aged 40 to 49 years, in the state of Paraná in comparison to the entire national territory. Using descriptive and quantitative methodology.